Gold complex QB1561 suppresses drug-resistant cancer cells by inhibiting TrxR and mitochondrial respiratory function - Hai-Ling Gao; Wenwen Ding; Zhi-Xin Shen; Qingbin Cui; Qingbin Cui (Frontiers in Pharmacology)
IntroductionMulti-drug resistance (MDR) is one of the leading reasons that cause the failures of cancer treatment. Novel agents that may reverse MDR and neutralize drug-resistant cancer cells are highly desirable for clinical practice. The targeting of cellular redox homeostasis and/or mitochondria-mediated energy metabolism are promising strategies for the suppression of drug-resistant cancer cells. Based on the structure of mono-gold(I) complex auranofin (AF), a drug candidate under clinical trials for cancer, we synthesized a new dual-gold(I) complex QB1561 and tested if it can inhibit drug-resistant cancer cells overexpressing ATP-binding cassette (ABC) transporters. We also investigated if QB1561 could inhibit thioredoxin reductase (TrxR), a well-known target of AF and other gold complexes, and assessed its impact on mitochondrial respiration.MethodologyCell viability of drug-resistant cells upon QB1561 alone or combined with topotecan and mitoxantrone was determined by MTS assay. The expression of ABC sub-family G member 2 (ABCG2) in the lung cancer cell line NCI-H460/MX20 after treatment with QB1561 was assessed by Western blot. The Vi-sensitive ABCG2 ATPase activity in the membrane vesicles of High Five insect cells, TrxR activity, and ROS production were measured following QB1561 treatment. Colony formation was used to assess QB1561’s anticancer potential. SeaHorce Seahorse XF Analyzers were used to measure the oxygen consumption rate (OCR).ResultsQB1561 suppressed the proliferation of drug-resistant cancer cells overexpressing ABC transporters, with IC50 values ranging from 0.57 to 1.80 μM, which was more effective than AF. QB1561 was able to partially reverse the resistance of mitoxantrone and topotecan in lung cancer NCI-H460/MX20 cells which overexpressed ABCG2, without altering the expression levels of ABCG2. QB1561 suppressed the colony formation of NCI-H460/MX20 cells, probably via ROS induction due to TrxR inhibition. QB1561 also efficiently suppressed OCR, suggesting its inhibition on mitochondrial respiration.ConclusionQB1561 was effective for the treatment of MDR in drug-resistant cancer cells. Its further evaluation could be useful for the design and development of more gold-based anticancer drugs.